2008
DOI: 10.1091/mbc.e08-01-0078
|View full text |Cite
|
Sign up to set email alerts
|

Variant-specific [PSI+] Infection Is Transmitted by Sup35 Polymers within [PSI+] Aggregates with Heterogeneous Protein Composition

Abstract: The [PSI(+)] prion is the aggregated self-propagating form of the Sup35 protein from the yeast Saccharomyces cerevisiae. Aggregates of Sup35 in [PSI(+)] cells exist in different heritable conformations, called "variants," and they are composed of detergent-resistant Sup35 polymers, which may be closely associated with themselves, other proteins, or both. Here, we report that disassembly of the aggregates into individual Sup35 polymers and non-Sup35 components increases their infectivity while retaining their v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
149
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(164 citation statements)
references
References 95 publications
(97 reference statements)
15
149
0
Order By: Relevance
“…6, C-F), including short barrel-like structures (Fig. 6E) that somewhat resembled structures from earlier attempts to visualize natural prion aggregates (51,52). When recovered protein was allowed to sit for several days at room temperature, some longer filamentous structures were observed including helical structures (Fig.…”
Section: Recovery Of Sds-resistant Prion Polymers For Morphologicalsupporting
confidence: 70%
See 1 more Smart Citation
“…6, C-F), including short barrel-like structures (Fig. 6E) that somewhat resembled structures from earlier attempts to visualize natural prion aggregates (51,52). When recovered protein was allowed to sit for several days at room temperature, some longer filamentous structures were observed including helical structures (Fig.…”
Section: Recovery Of Sds-resistant Prion Polymers For Morphologicalsupporting
confidence: 70%
“…Sis1, along with other chaperones, is known to be associated with Rnq1 prion aggregates (51), and mutations in SIS1 can affect Rnq1 aggregation (45,46). Yet, no other chaperones were identified by TAPI, implying that among chaperones Sis1 has the strongest binding or a distinct mode of binding to prion aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…At a molecular level, excess Ssa increases both the size of Sup35 polymers and the proportion of non-aggregated Sup35 (Allen et al 2005). Ssa physically interacts with Sup35 (Allen et al 2005) and was identified as a major non-Sup35 component associated with [PSI + ] aggregates in vivo (Bagriantsev et al 2008). Excess Ssb also antagonizes weak variants of [PSI + ] upon prolonged propagation (Kushnirov et al 2000b;Chacinska et al 2001) or other [PSI + ] variants in the presence of excess Sup35 (Allen et al 2005).…”
Section: Role Of Other Hspsmentioning
confidence: 99%
“…Ure2 fibers were identified in [URE3] cells overexpressing Ure2 with EM (Speransky et al 2001 (Bagriantsev et al 2008). The fluorescent rings and dots formed in the process of prion induction by overexpressed Sup35-GFP (see Prion induction by overproduction) were shown to be made of fibrils (Tyedmers et al 2010).…”
Section: Models Of Prion Structuresmentioning
confidence: 99%
“…129 Moreover, proteins regulating the assembly and disassembly of actin filaments involved in formation of endocytic vesicles, such as for example Sla1, Sla2 and End3 interact with prion aggregates. [64][65][66]130 It was suggested that particularly during de novo formation of the [PSI + ] prion, the misfolded prion determinants, e.g., Sup35 or NM-GFP, associate with the cytoskeleton, which may facilitate local concentration and subsequently conformational conversion 131 of the prion determinants to the prion state. 65,86 A possible molecular link between the actin cytoskeleton and prion aggregates, especially during stress induced prion formation, is the stress-inducible protein Lsb2.…”
Section: Prion Deposition Sites In Yeastmentioning
confidence: 99%